ANALISIS DAMPAK BROKEN HOME TERHADAP MINAT BELAJAR SISWA SMA SANTUN UNTAN PONTIANAK - Roy Novianto; Amrazi Zakso; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research is motivated by the problem of broken home that affects family children, in their interest in learning at school. This study was intended to study the thoughts of destroyed houses on the learning interest of SMA Santun Untan Pontianak students. The method in this study was descriptive in the form of qualitative research. The data sources in this study were students from broken home families. Data collection techniques in this study was donethrough interviews, observation and documentation. The analysis in this study was presented in a qualitative descriptive manner using three informants. The results of this study indicate that students who come from broken families have academic problems and behavioral problems and some do not experience them. Students' interest in learning from families is broken. There were students who have interest in learning, and students who have no interest in learning because they have a family background. The conclusions of this study were students who came from damaged families, which were considered positive and negative from damaged homes. The learning interest of students who come from families was divided, there are those who have an interest in learning and who are not interested in learning. Keywords: Broken Home, Family,Learning Interest